A Study on Comprehensive Evaluation of Multiple-depth Sea Water Quality in the South China Sea. Issue 1 (July 2021) - Ma, Xiaolei; Duan, Mengshan; Duan, Duomo; Qiu, Jinquan; Cao, Junrui
Abstract: During the investigation in the South China Sea in the summer of 2018, the sea water samples were for temperature, salinity, dissolved oxygen, pH, nutrient salts (NO3 -N, NO2 -N, NH4 -N, PO4 -P, SiO3 -Si), essential elements (Na, K, Mg, Ca, Sr, Cl, Br, B), trace elements (Cu, Zn, Fe Mn, Ni, Se, Mo, Co and V), heavy metal (Hg, Pb, As, Cd), organic elements (TOC, DOC, GOC), chlorophyll and microorganisms analyses from different layers of 12 stations according to the standard sampling specifications. The seawater samples of different depths were directly measured by inductively coupled plasma mass spectrometry. The distribution of several elements in the South China Sea water was investigated. It could be seen from the analytical results that the water temperature, salinity, pH, dissolved oxygen, the content of NO3 -N, PO4 -P, SiO3 -Si, K +, Mg 2+, Ca 2+, Sr 2+, Cl -, Br -, B 3+, Zn, Mn, V, Cr, GOC and Chlorophyll was significantly correlated with depth of seawater.